THE NEW FACE OF AN OLD TOXIN: BOTULINUM TOXIN IN THE PREVEN-TION OF POST-OPERATIVE HEART RHYTHM DISORDERS - Anna Kaźmierska; Maciej Kaźmierska (International Journal of Innovative Technologies in Social Science, 2025)
Botulinum toxin, previously used mainly in neurology and aesthetic medicine, is increasingly finding application in new fields, including cardiology. Its ability to selectively and temporarily block cholinergic conduction makes it a promising tool for modulating the activity of the autonomic nervous system, which is important in the prevention of postoperative atrial fibrillation (POAF). Atrial fibrillation is one of the most common postoperative complications in cardiac surgery, significantly affecting the course of recovery and patient prognosis. An imbalance between sympathetic and parasympathetic regulation of the heart rhythm plays a significant role in the pathogenesis of this disorder. This paper reviews the current state of knowledge on the therapeutic potential of botulinum toxin in the prevention of POAF. The data indicate that the use of botulinum toxin may lead to a reduction in the incidence of postoperative arrhythmias in selected patient groups. The need for further research to determine the optimal treatment regimen and identify the patient population most likely to benefit from this type of therapy was also emphasised.